В)4х+2х-7=5 е)8=3х-х
6x=12 2x=8
x=2 х=4
√ ( 2x - 1 ) + ( 2x - 1 ) = 2
√ 2x - 1 = a
a ≥ 0
a + a² = 2
a² + a - 2 = 0
D = 1 + 8 = 9 ; √ D = 3
a1 = ( - 1 + 3 ) : 2 = 1
a2 = ( - 1 - 3 ) : 2 = - 2 ( ≤ 0 )
√ ( 2x - 1 ) = 1
( √ ( 2x - 1 ))² = 1²
2x - 1 ≥ 0
2x ≥ 1
x ≥ 0,5
2x - 1 = 1
2x = 2
x = 1
Ответ 1
Ответ:
1) 7.8a+2.3a-5a=5.1a
a=6
5.1a*6=30.6
2) 2(0.3b+5)+1.4b=0.6b+10+1.4b=2b+10
b=4
2b+10=8+10=18
3) 6(a+5)-2.8a=6a+30-2.8a=3.2a+30
a=1.5
3.2a+30=4.8+30=34.8
4) 4(b+0.8)+1.7b=4b+3.2+1.7b=5.7b+3.2
b=2.3
5.7b+3.2=13.11+3.2=16.41
Подробнее - на Znanija.com - znanija.com/task/29743304#readmore
Пошаговое объяснение: